Asymmetric Transfer Hydrogenation Catalyzed by Mesoporous MCM-41-Supported Chiral Ru-Complex - Sarkar, Shaheen M.; M. M., Yusoff; Lutfor, M. R. (John Wiley & Sons, Inc., 2014)
Chiral N-sulfonyldiamine was successfully anchored on mesoporous MCM-41 silica. The MCM-41-supported chiral N-sulfonyldiamine was used as an efficient heterogeneous chiral ligand in the asymmetric transfer hydrogenation of ketones. This heterogeneous system offered satisfactory enantioselectivities up to 94% with excellent conversions.